2017
DOI: 10.1016/j.archoralbio.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of odontogenic ameloblast-associated protein in the dental follicle and its role in osteogenic differentiation of dental follicle stem cells

Abstract: Objective Odontogenic Ameloblast-Associated Protein (ODAM) is encoded by a secretory calcium-binding phosphoprotein cluster gene, which generally plays an important role for mineralization. Dental follicle (DF) is essential in regulating bone formation for tooth eruption. This study aims to reveal ODAM expression in the DFs of developing and erupting molars, and to determine the possible role of ODAM. Design DFs were collected from human third molars and rat mandibular molars for gene expression assessment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Wise et al [34] reported that nonstem DFCs would be gained when cultured in MEM and 10% Gibco newborn calf serum with antibiotics, indicating that DFC cultures derived from this condition are fibroblast-like cells [34] and do not possess the capability of differentiation [37]. Yao et al [37,38] reported that primary cultured cell populations derived from dental tissue contained stem cells when cultured in medium consisting of a-MEM plus 20% FBS and proper antibiotics, indicating that our isolated primary DFCs and ABM-MSCs derived from this condition contained stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Wise et al [34] reported that nonstem DFCs would be gained when cultured in MEM and 10% Gibco newborn calf serum with antibiotics, indicating that DFC cultures derived from this condition are fibroblast-like cells [34] and do not possess the capability of differentiation [37]. Yao et al [37,38] reported that primary cultured cell populations derived from dental tissue contained stem cells when cultured in medium consisting of a-MEM plus 20% FBS and proper antibiotics, indicating that our isolated primary DFCs and ABM-MSCs derived from this condition contained stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies supported that glutamine metabolism as a regulatory node participated in many biological processes, including vessel formation, cancer progress, and immune regulation [1416]. Recently, glutamine in bone homeostasis gained increasing concentration in mediating the proliferation, osteoblast, and adipocyte differentiation, immunological features of cell BMSCs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Ameloblast-associated protein (OADM) related to mineralization expressed on DFCs in a time-dependent pattern. The gradually increased OADM expression in the early stage of differentiation accelerated osteogenesis to make a normal eruption, and the missing OADM did not influence bone density but resulted in a postponed tooth eruption [54, 55]. Cleidocranial dysplasia (CCD) patients are characterized by delayed tooth eruption due to runt-related transcription factor 2 ( Runx2 ) mutation, DFCs-CCD patients displayed significantly lower osteogenic, osteoclast-inductive and matrix-degrading capacities, mechanistically contacted with disturbed RANK/RANKL/OPG signaling and decreased expression of matrix metalloproteinase 9 (MMP9) and MMP2 [5658].…”
Section: Dfcs In Tooth Developmentmentioning
confidence: 99%
“…The level of EGR1 was elevated after osteogenic differentiation of DFCs and in turn it regulated the expression of DLX3 and BMP2 to mediate osteogenic differentiation positively [96]. Fractional odontogenic matrix protein such as dentin matrix protein 1 (DMP1) and odontogenic ameloblast-associated protein (ODAM) have been identified to correlate positively with the osteogenic capability of DFCs, which suggested the complex microenvironment in different time and space for DFC differentiation in tooth development [54, 97].…”
Section: Multipotent Differentiation Of Dfcsmentioning
confidence: 99%